2014
DOI: 10.1016/j.artint.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting good teaching from humans for machine learners

Abstract: Interactive machine learningWe propose using computational teaching algorithms to improve human teaching for machine learners. We investigate example sequences produced naturally by human teachers and find that humans often do not spontaneously generate optimal teaching sequences for arbitrary machine learners. To elicit better teaching, we propose giving humans teaching guidance, which are instructions on how to teach, derived from computational teaching algorithms or heuristics. We present experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…The ability to analyse teaching behaviour is critical to improving LfD performance. It can be shown that an optimal teacher can theoretically provide the minimum number of samples required to teach a learner a task, called the teaching dimension (Goldman and Kearns, 1995;Balbach and Zeugmann, 2009;Khan et al, 2011;Cakmak and Thomaz, 2014;Zhu, 2015), by providing non-i.i.d. samples to the learner which exploit the task structure and learning method employed.…”
Section: Insights From Machine Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to analyse teaching behaviour is critical to improving LfD performance. It can be shown that an optimal teacher can theoretically provide the minimum number of samples required to teach a learner a task, called the teaching dimension (Goldman and Kearns, 1995;Balbach and Zeugmann, 2009;Khan et al, 2011;Cakmak and Thomaz, 2014;Zhu, 2015), by providing non-i.i.d. samples to the learner which exploit the task structure and learning method employed.…”
Section: Insights From Machine Teachingmentioning
confidence: 99%
“…can be attributed to teachers lacking a shared mental model with the robot, or a lack of understanding of how and what the robot learns during the teaching process (Cakmak and Thomaz, 2014;Hellström and Bensch, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although interactive robots can outperform passive ones in both performance and quality of the interaction, a careful design of the Human-Robot interaction (HRI) is needed. Aspects like the transparency of the robot learning process [11,33], the ability of the user to be a good teacher [9], the timing of the queries or the balance in control over the interaction [7] must be taken into account. Furthermore, efficient ways to mediate between the robot's internal skill representation and the user need to be crafted.…”
Section: Introductionmentioning
confidence: 99%
“…Videos are used for experiment instruction to help ensure consistency in the participants' prior knowledge for each teaching phase, and to remove the risk of the researcher providing more or less information on how to complete the task between participants. Additionally, as noted in [13], video instruction is a highly effective teaching tool for novice users.…”
Section: B Training Proceduresmentioning
confidence: 99%